2014
DOI: 10.1371/journal.pone.0087301
|View full text |Cite
|
Sign up to set email alerts
|

Binding Sites Analyser (BiSA): Software for Genomic Binding Sites Archiving and Overlap Analysis

Abstract: Genome-wide mapping of transcription factor binding and histone modification reveals complex patterns of interactions. Identifying overlaps in binding patterns by different factors is a major objective of genomic studies, but existing methods to archive large numbers of datasets in a personalised database lack sophistication and utility. Therefore we have developed transcription factor DNA binding site analyser software (BiSA), for archiving of binding regions and easy identification of overlap with or proximi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…It is designed to identify factors that target the same genomic locations. As described in examples in our previous study ( Khushi et al, 2014 ) the OCV should be greater than 0.5 for partner factors, reflecting a statistically significant correlation between two binding patterns. For example the OCV for known partners, FOXA3 (query) to FOXA1 (reference) was 0.72 ( Motallebipour et al, 2009 ).…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…It is designed to identify factors that target the same genomic locations. As described in examples in our previous study ( Khushi et al, 2014 ) the OCV should be greater than 0.5 for partner factors, reflecting a statistically significant correlation between two binding patterns. For example the OCV for known partners, FOXA3 (query) to FOXA1 (reference) was 0.72 ( Motallebipour et al, 2009 ).…”
Section: Discussionsupporting
confidence: 59%
“…In summary, we have evidence for a biologically relevant interplay between PR and ER α in a subset of binding sites in breast cancer cells. Our analysis demonstrated the utility of our previously published software BiSA ( Khushi et al, 2014 ), which has a comprehensive knowledge base, consisting of transcription factor binding sites and histone modifications collected from previously published studies. Using BiSA we identified that ER α and PR co-locate on a subset of binding sites.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations